The formation of Islamic art - Grabar, Oleg (Yale University Press, 1987)
This classic work on the nature of early Islamic art has now been brought up to date in order to take into consideration material that has recently come to light. In a new chapter, Oleg Grabar develops alternate models for the formation of Islamic art, tightens its chronology, and discusses its implications for the contemporary art of the Muslim world.